Pemberdayaan Potensi Kewirausahaan Melalui Digital Marketing Desa Karang Gading Kecamatan Secanggang - Rizky Fatmawati (Maslahah: Jurnal Pengabdian Masyarakat, 2021)
Digital marketing is an activity to promote and find markets through digital media online by using various means such as social networks. Digital marketing uses the application of digital technology. One form of digital marketing using electronic media or the internet is internet marketing (e-marketing). The focus of this community service activity is on empowering the entrepreneurial potential of local products through digital marketing in Karang Gading Village, Secanggang District. Community service activities are carried out through seminar activities that aim to provide an understanding of the village apparatus and the community in empowering the entrepreneurial potential of local products through digital marketing in Karang Gading Village, Secanggang District.